1997
DOI: 10.1292/jvms.59.361
|View full text |Cite
|
Sign up to set email alerts
|

Variation from Cytopathogenic Biotype to Non-Cytopathogenic Biotype is Correlated with the Deletion of Cellular Sequence from Bovine Viral Diarrhea Viruses.

Abstract: ABSTRACT. Non-cytopathogenic (NCP) viruses of bovine viral diarrhea (BVD) virus were detected at a low ratio by the reverse plaque formation method from virus samples after several plaque clonings of cytopathogenic (CP) BVD viruses; NADL and Osloss strains. This phenomenon suggests that the NCP BVD viruses are produced at a low ratio during the propagation of CP BVD viruses in vitro. To investigate the differences between the parent CP BVD virus and the NCP BVD virus as a real progeny, the regions flanking the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The noncp pestiviruses replicate without inducing a cytopathic effect (CPE), while cp viruses cause lysis of appropriate cultured cells. Cytopathogenic viruses are frequently reported for BVDV and some cp BVDVs have insertions of cellular sequences, duplication of the viral genome, or contain defective interfering (DI) particles [16,20,21]. Most CSFV field isolates that show the exaltation of Newcastle disease virus (END) phenomenon [8] are noncp in porcine cell cultures.…”
mentioning
confidence: 99%
“…The noncp pestiviruses replicate without inducing a cytopathic effect (CPE), while cp viruses cause lysis of appropriate cultured cells. Cytopathogenic viruses are frequently reported for BVDV and some cp BVDVs have insertions of cellular sequences, duplication of the viral genome, or contain defective interfering (DI) particles [16,20,21]. Most CSFV field isolates that show the exaltation of Newcastle disease virus (END) phenomenon [8] are noncp in porcine cell cultures.…”
mentioning
confidence: 99%
“…Some preparations of cp BVDVs have insertions of cellular sequences, duplication of the viral genome in their genome, or defective interfering (DI) particles [17,22]. Recently, it has been reported that some strains of CSFV, which do not show the exaltation of Newcastle disease virus (END) phenomenon [10] but show intrinsic interference [5], inducing CPE in some swine kidney cell lines [24,26].…”
mentioning
confidence: 99%
“…Bovine testicle (BT) cells used for propagation of viruses, viral titration and serum neutralizing test were grown in Eagle's minimum essential medium supplemented with 10% fetal calf serum (GM) [18]. All cell cultures and fetal calf serum were determined to be free of BVDV before use by RT-PCR [14].…”
Section: Cell Culture and Virusesmentioning
confidence: 99%